2013
DOI: 10.1044/1059-0889(2013/12-0072)
|View full text |Cite
|
Sign up to set email alerts
|

Masking Release Due to Linguistic and Phonetic Dissimilarity Between the Target and Masker Speech

Abstract: Purpose To investigate masking release for speech maskers for linguistically and phonetically close (English and Dutch) and distant (English and Mandarin) language pairs. Method Twenty monolingual speakers of English with normal-audiometric thresholds participated. Data are reported for an English sentence recognition task in English, Dutch and Mandarin competing speech maskers (Experiment I) and noise maskers (Experiment II) that were matched either to the long-term-average-speech spectra or to the temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 19 publications
8
47
0
Order By: Relevance
“…We show that unattended NV speech becomes more distracting when intelligible (after training) compared to when it is poorly understood (prior to training) and that these effects appear more prominent at SNR À3 dB. In line with past reports (Brouwer et al, 2012;Brungart, 2001;Calandruccio et al, 2013;Hoen et al, 2007;Iyer et al, 2010;Lecumberri and Cooke, 2006;Lecumberri et al, 2010;Rhebergen et al, 2005;Van Engen and Bradlow, 2007), the present results show that an intelligible distractor interferes more with the processing of target speech and suggest that speech-in-speech interference originates, to a certain extent, from the parallel processing of competing linguistic content.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We show that unattended NV speech becomes more distracting when intelligible (after training) compared to when it is poorly understood (prior to training) and that these effects appear more prominent at SNR À3 dB. In line with past reports (Brouwer et al, 2012;Brungart, 2001;Calandruccio et al, 2013;Hoen et al, 2007;Iyer et al, 2010;Lecumberri and Cooke, 2006;Lecumberri et al, 2010;Rhebergen et al, 2005;Van Engen and Bradlow, 2007), the present results show that an intelligible distractor interferes more with the processing of target speech and suggest that speech-in-speech interference originates, to a certain extent, from the parallel processing of competing linguistic content.…”
Section: Discussionsupporting
confidence: 90%
“…Some evidence suggests that distracting signals have dissociable masking effects on target speech comprehension depending on their amount of linguistic information. For example, distracting speech impairs the processing of target speech more strongly than does other unintelligible noise [e.g., noisevocoded (NV) speech, rotated speech, time-reversed speech] (Brungart, 2001;Calandruccio et al, 2013;Hoen et al, 2007;Rhebergen et al, 2005); native distracting speech is a stronger distractor than non-native or unknown speech (Brouwer et al, 2012;Rhebergen et al, 2005;Van Engen and Bradlow, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This result was even observed when the unintelligible (unfamiliar language) masking speech was produced by the same talker in phrases with comparable spectrotemporal properties to those used for the intelligible (native language) masking speech (Freyman, Balakrishnan, & Helfer, 2001). Subsequent research suggested that part of the difficulty arose from the linguistic similarity of the target and masking languages, such that listeners experienced greater interference from maskers that were linguistically more similar to the language of the target stimuli (Calandruccio, Brouwer, Van Engen, Dhar, & Bradlow, 2013). Moreover, studies with bilingual listeners showed that such effects of masker intelligibility were likely gradient and depended at least in part on the listener's proficiency in the second language.…”
Section: Target-masker Linguistic Similarity and Language Experiencementioning
confidence: 98%
“…These comparisons can thus give insight into contextual influences (i.e., the context surrounding the critical test trials in one experimental run) on speech-in-speech recognition, taking into account the relative degrees of language masking of the test and surrounding trials. We selected English and Dutch as the languages for this study because our previous work has shown the target-background language mismatch benefit with this language pair, and the current study is part of this series of studies that have used this pair (Brouwer et al, 2012;Calandruccio et al, 2013). Furthermore, our previous work has shown a smaller masking release when a masker language is more linguistically close to the target speech than when it is distant (Calandruccio et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We selected English and Dutch as the languages for this study because our previous work has shown the target-background language mismatch benefit with this language pair, and the current study is part of this series of studies that have used this pair (Brouwer et al, 2012;Calandruccio et al, 2013). Furthermore, our previous work has shown a smaller masking release when a masker language is more linguistically close to the target speech than when it is distant (Calandruccio et al, 2013). In the current study, we created a situation of potentially high confusion between target and masker signals by choosing Dutch as the mismatched language masker as this language is relatively linguistically close to English (the language of the targets).…”
Section: Introductionmentioning
confidence: 99%